Theoretical problems and the concept of state administrating the branch of health care in the social system (Journal of actual problems of jurisprudence, 2018)
The article is investigated the theoretical problems and the concept of state administrating the branch of health care in the social system.Special aspects of state administrating the branch of health care and the problems of the legal regulation are considered. The recommendations connected with improving the public administration of the health care of the Republic of Kazakhstan are given.Key words: health, government, law, system, management, social.